Effects of alfalfa (fresh, silage, hay) on the fatty acid and conjugated linoleic acid amounts in lamb muscles and fats - Ciftci, M.; Cerci, I. H.; Kilinc, U.; Yilmaz, O.; Gurdogan, F.; Seven, P. T.; Ozcelik, M. (Ecole Nationale Veterinaire Toulouse, 2010)
The aim of this study was to investigate the effects of fresh, ensiled and dried alfalfa on the meat quality of lamb. For this purpose, 40 Akkaraman, 4 months old, lambs were divided into 4 equal groups according to the dietary treatments: control lambs were fed with wheat straw whereas the ration of all other animals were based on alfalfa in a fresh, silage or dried form (groups AF, AS and AD, respectively) for 98 days, then the fatty acid composition of the rations and in muscles (semi-membranosus, longissimus dorsi, deltoideus and gluteobiceps) and fats (tail and subcutaneous fats) were determined by gas chromatography. Alfalfa exhibited a lower saturated fatty acid (SFA) and higher polyunsaturated fatty acid (PUFA) contents than wheat straw. In parallel, tissue SFA concentrations in muscle and fat were significantly higher in controls, whereas significantly highest PUFA amounts were recorded in lambs fed with alfalfa mainly in the fresh form. The proportions of omega 3 and omega 6 fatty acids, such as the linolenic acid and the linoleic acid respectively, as well as the CLA proportions were significantly and markedly increased in fats and in muscles (except for w3 content in the gluteobiceps) from lambs fed with alfalfa whatever its distribution form. These results demonstrate that the utilization of alfalfa forage in the lamb ration significantly improved the fat composition of meat.
Keywords: Alfalfa; lamb meat; fat; muscle; saturated fatty acids; polyunsaturated fatty acids; linoleic acid; conjugated linoleic acid